Determination of potentially novel compensatory mutations in rpoC associated with rifampin resistance and rpoB mutations in Mycobacterium tuberculosis clinical isolates from Peru - Vargas Ruiz, Ana Paula (2020)
Background: Rifampicin (RIF) resistance in Mycobacterium tuberculosis is frequently caused by mutations in the rpoB gene. These mutations are associated with a fitness cost, which can be overcome by compensatory mutations in other genes, among which rpoC may be the most important. Aims and objectives: We analyzed 469 Peruvian M. tuberculosis clinical isolates to identify compensatory mutations in rpoC/rpoA associated with RIF resistance. Materials and methods: The M. tuberculosis isolates were collected and tested for RIF susceptibility and spoligotyping. Samples were sequenced and aligned to the reference genome to identify mutations. By analyzing the sequences and the metadata, we identified a list of rpoC mutations exclusively associated with RIF resistance and mutations in rpoB. We then evaluated the distribution of these mutations along the protein sequence and tridimensional structure. Results: One hundred and twenty‑five strains were RIF susceptible and 346 were resistant. We identified 35 potential new compensatory mutations, some of which were distributed on the interface surface between rpoB and rpoC, arising in clusters and suggesting the presence of hotspots for compensatory mutations. Conclusions: This study identifies 35 putative novel compensatory mutations in the β’ subunit of M. tuberculosis RNApol. Six of these (S428T, L507V, A734V, I997V, and V1252LM) are considered most likely to have a compensatory role, as they fall in the interaction zone of the two subunits and the mutation did not lead to any change in the protein’s physical– chemical properties.